Understanding of disaster preparedness by elementary school teachers and directions for counseling guidance services in elementary schools - Kusnarto Kurniawan; S Sunawan; Dian Purbo Utomo; Abdul Kholiq; Vrimadieska Ayuanissa Waluyan (KONSELOR, 2023)
Understanding of disaster preparedness includes knowledge and mastery of the efforts that can be taken to anticipate or reduce disaster risk. The purpose of the study is to analyze the understanding of disaster preparedness by elementary school teachers and the direction of counseling and guidance services in elementary schools. This study uses a descriptive method with a quantitative approach. The research instrument is the scale of understanding disaster preparedness and a questionnaire on the direction of Guidance and Counseling services. The study population was elementary school teachers in the Teacher Working Group (KKG) Pringgondani Group Coordinator of the Education Unit (Korsatpen) Banyumanik District, amounting to 35 people. Sampling through total sampling technique so that the entire population becomes the research sample. Data analysis was carried out using descriptive statistics. The results showed that elementary school teachers at the KKG Pringgondani Group Korsatpen Banyumanik District had a high level of understanding of disaster preparedness. The implementation of Guidance and Counseling services in elementary schools is aimed at assisting students in realizing disaster preparedness through basic service components, individualized planning and specialization services, responsive services, and support system. The results of the study are expected to be used as material for student learning activities to realize an understanding of disaster preparedness by elementary school teachers through Guidance and Counseling services in elementary schools and their service program components.